Kepraktisan Video Pembelajaran Kalkulus untuk Fisika dalam Proses Belajar Daring pada Masa Pandemi Covid-19 - Rahmat Hidayat; Putri Dwi Sundari; Fadhila Ulfa Jhora; Hidayati Hidayati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Corona virus disease (covid-19) has spread all over the world and became a pandemic in short time. Indonesia is one of the countries that affected by covid-19 pandemic. Covid-19 changed everything in various area including education. Online learning became one of the solutions in universities in order to keep learning process going. Unfortunately, policy to apply online learning is facing many difficulties associated with infra-structure, student economic capability and time management. Learning video is presented to overcome difficulties of online learning during covid-19 pandemic in subject of Calculus for Physics. The video presents material supported by sample problem and solution. Practicality of the learning video was examined by collecting student`s responses in aspect of ease of use, learning time efficiency, attractiveness and benefits. Data was analyzed using percentage formula to determine criteria of practicality. The result of the observation revealed that learning video of calculus for physics has a good practicality that represented by score of each aspects of 81,26% for ease of use, 83,53% for learning time efficiency, 79,87% for attractiveness and 81,08% for benefits. Based on this result we conclude that learning video is very useful to assist student in online learning during covid-19 pandemic. Furthermore, learning video could be one of the best choices in learning media to apply digital and remote learning in facing of Industrial Revolution 4.0.